2013
DOI: 10.1021/ml400304w
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Human Acetylcholinesterase Bound to Dihydrotanshinone I and Territrem B Show Peripheral Site Flexibility

Abstract: Acetylcholinesterase is a critical enzyme that regulates neurotransmission by degrading the neurotransmitter acetylcholine in synapses of the nervous system. It is an important target for both therapeutic drugs that treat Alzheimer's disease and chemical warfare agents that cripple the nervous system and cause death through paralysis. The enzyme has both catalytic and peripheral sites to which inhibitors may bind. Structures of recombinant human acetylcholinesterase in complex with the natural product inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
154
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(159 citation statements)
references
References 34 publications
4
154
0
1
Order By: Relevance
“…'s seminal X-ray crystal structure of human AChE [ h AChE] bound with (+)-territrem-B [TB]. 24 Their reported structure is almost in exclusive agreement with our model [ vide infra ]. 1 Encouraged by this success, we expanded our modeling studies to the arisugacin and territrem families of natural products as well as a series of de novo analogs focusing on the E-ring.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…'s seminal X-ray crystal structure of human AChE [ h AChE] bound with (+)-territrem-B [TB]. 24 Their reported structure is almost in exclusive agreement with our model [ vide infra ]. 1 Encouraged by this success, we expanded our modeling studies to the arisugacin and territrem families of natural products as well as a series of de novo analogs focusing on the E-ring.…”
supporting
confidence: 76%
“…Specifically, the reported TB– h AChE 24 bound structure appears to better accommodate arisugacin-like structures with a large degree of reorganization around the catalytic active site and protein backbone in the peripheral site that led to an altered gorge shape. 24 Our modeling study employed AutoDock v4.2 and the more recent version in AutoDock Vina , 4 made available by The Scripps Research Institute under a General Public License.…”
mentioning
confidence: 98%
“…Attempts to obtain a crystal structure of the hopeahainol A-AChE complex, either by diffusing hopeahainol A into human AChE crystals (e.g., [22]) or by crystallizing the complex directly, were unsuccessful. Crystals that were soaked in 1.3 mM hopeahainol A for four days showed no evidence of ligand binding and seemed to diffract just as well as those that were never soaked.…”
Section: Resultsmentioning
confidence: 99%
“…These include aflatoxin B1, dihydrotanshinone I, and territrem B. Using an inhibitor competition assay that can distinguish whether an inhibitor is bound to the A-site or the P-site and X-ray crystallography, we showed that aflatoxin B1 and dihydrotanshinone I bound specifically to the P-site while territrem B spanned the P- and A-sites [1, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of human AChE (PDB ID: 4M0E) 30 was downloaded from protein data bank (PDB) database. 31 The protein was prepared via inserting missing atoms in incomplete residues, modeling missing loop regions, deleting alternate conformations (disorder), adding hydrogens, removing waters, standardizing atom names, etc., and energy minimization was performed using the CHARMm forcefield.…”
Section: Molecular Docking Studymentioning
confidence: 99%